Pengaruh Air Perasan Buah Jeruk Nipis (Citrus Aurantifolia Swingle) Terhadap Hambatan Pertumbuhan Bakteri Enterococcus Faecalis Dominan Pada Saluran Akar Secara In Vitro - Yahya, Hilmi, drg. Fitria Nur Malita Sari (2016)
Root canal treatment is a treatment of pulp disease by taking the pulp tissue and replace it with obturation material. Irrigation of root canal is an important step in root canal treatment procedure. One aim of irrigation is to eliminate bacteria in root canal. Enterococcus faecalis is majority a group of bacteria found from periapical infection after root canal treatment. Clorhexidine 2% is an irrigant that used to desinfect root canal. Chlorhexidine 2% have a side effects, such as teeth discoloration and irritation of the mucous, so that required an alternative irrigant which can be safer to use. Lime juice (Citrus aurantifolia S.) is a natural material that has an antibacterial activity because it contain a several active substances, such as citric acid, flavonoid, and limonene. The aim of this study was to determine the effect of lime juice (Citrus aurantifolia S.) on Enterococcus faecalis growth inhibition, determine the concentration of lime juice (Citrus aurantifolia S.) which has the largest Enterococcus faecalis growth inhibition, and compare inhibitory of lime juice (Citrus aurantifolia S.) with chlorhexidine 2%. The type of this research was purely experimental laboratory. This study uses diffusion wells method consisting of four treatment groups, ie lime juice in concentration 25%, 50%, 100%, and chlorhexidine 2% (positive control). Each treatment group replicated 6 times. Inhibition zone measured by using calipers in millimeter (mm). The results showed that lime juice (Citrus aurantifolia S.) has an antibacterial activity in the presence of inhibitory zone at a concentration 25% (d = 5.09 mm), 50% (d = 8.72 mm), and 100% (d = 13.52 mm). One way Anova test results showed the value of p=0.000 (p <0.05), so it can be concluded that lime juice has an effect on Enterococcus faecalis growth inhibition in vitro. Lime juice (Citrus aurantifolia S.) has the largest Enterococcus faecalis growth inhibition at a concentration 100%. Chlorhexidine 2% (positive control) has a larger Eterococcus faecalis growth inhibition than lime juice (Citrus aurantifolia S.) in concentration 25%, 50% and 100%.